Constructed Wetlands for Remediation of Urban Waste Waters - Berezowsky, Miron (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1995)
Summary This paper provides a brief review of the characteristics of artificially constructed wetlands and their use in remediating water quality, principally in connection with municipal waste waters, urban storm-water run off, and acid mine drainage. In the past 15 years, a heightened interest in the application of both natural and constructed wetland treatment for water quality improvement has resulted in the construction of more than 1500 wetland systems worldwide.This rapid growth appears to be part of a global movement that supports more resource conservation and greater reliance on natural ecological processes in preference to the energy- and chemical-intensive systems currently in use.